Analisis Pengelolaan Keuangan Pada Usaha Mikro Kecil Dan Menengah (UMKM): Studi Kasus Pada Usaha Konveksi Di Kecamatan Binawidya Kota Pekanbaru - Lufi Erisanti; Febrina Rita Albeta (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the application of financial management in Micro, Small and Medium Enterprises (MSMEs), especially in convection businesses in Binawidya District, Pekanbaru City. MSMEs have a strategic role in supporting local and national economic growth, but often face obstacles in effective and professional financial management. This research uses a qualitative approach with a case study method, where data is collected through interviews, observations, and documentation of 10 (ten) informants of business actors engaged in Convection Businesses. The results showed that financial management in Convection Businesses in Binawidya District, Pekanbaru City had implemented, but still could not be said to be perfect. The results show that of the 4 indicators of financial management, only the Budget Planning, Recording and Control indicators have been implemented properly. As for the reporting indicator, it is still not well implemented. Implementation is still not running optimally because MSME actors in the convection sector experience various problems, such as lack of knowledge in making financial reports and low awareness of the importance of evaluating financial performance. Continuous training and guidance are needed to improve managerial skills in terms of their finances.